Physico-chemical characterization of food grade natural spring salt from the Central Anatolia region of Turkey and investigation of its microplastic content - Ogün Bozkaya
Delice salt is a natural spring salt obtained from the evaporation of spring water from the Central Anatolia region of Turkey and is a food grade salt with a geographical indication certificate. The aim of this study was to evaluate the compliance of Delice natural spring salt (Delice NSS), a commercial product, with food grade criteria by physicochemical characterizations and to investigate whether it contains microplastics. The NaCl%, moisture suspended solids and acid insoluble matter contents of Delice NSS were analyzed and determined as 98.79% (w/w), 0.301% (w/w), 0.16% (w/w) and 0.01% (w/w), respectively. Sodium, other minerals, and heavy metals were analyzed by inductively coupled plasma-optical emission (ICP-OES) spectrometry. In addition, fluoride, nitrate, and sulphate ions were analyzed by ion chromatography (IC). The chemical and thermal properties of Delice NSS were characterized by FTIR, X-ray fluorescence (XRF) and thermogravimetric analyzer (TGA). Moreover, Delice NSS was investigated whether it contains microplastics and some particles were detected under fluorescence microscopy. However, it was concluded that particles were not microplastics after TGA and FTIR analyses. The results revealed that Delice NSS does not carry a risk in terms of physicochemical properties as a foodstuff.